Profile of Analgesics in Toddler Patients Undergoing Surgery at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, January 2021-December 2021 - Devin Hernando; Maulydia Maulydia; Mohammad Fathul Qorib; Kohar Hari Santoso (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: Pain is the most common complaint in every medical procedure. Pain management in toddlers requires special attention due to the need to consider various factors.   Abstract Introduction: Pain is the most frequent complaint in all medical procedures. Managing procedures in toddlers requires special attention due to various influencing factors. The 19th century witnessed significant advancements in analgesics. Analgesics help manage pain that may arise from procedures performed on toddlers. Methods: This study identified the analgesic profile in toddlers undergoing surgery at the Integrated Surgery Center (GBPT) of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January to December 2021. It was a retrospective descriptive study using medical records. The sample included toddlers who underwent surgery and received analgesics at Dr. Soetomo General Academic Hospital in Surabaya, Indonesia. The sampling technique used was total sampling. Results: During January to December 2021, a total of 451 pediatric patients underwent surgery at Dr. Soetomo General Academic Hospital in Surabaya, Indonesia. A total of 232 patients were excluded due to incomplete medical records. A total of 219 patients met the criteria. The majority were 1-year-old (32.42%), with male patients being predominant (58.9%). Most toddlers had a normal body mass index (BMI). The majority of surgeries lasted 1-3 hours (64.38%). The most common procedures were debridement and wound dressing (11.87%). Opioids were the most frequently used analgesics (41%), with fentanyl being the most common (71.85%), while paracetamol was the primary non-opioid analgesic (43.33%). The most common pain intensity before and after surgery was no pain. Conclusion: Analgesics help manage procedural pain in toddlers. Opioids were the most frequently used, with fentanyl being the most common.